Determinants of the nonperforming loans of Nigerian deposit money banks - Wasiu Abiodun Sanyaolu; Trimisiu Tunji Siyanbola; Hafeez Babatunde Makinde (Economic Horizons, 2020)
Credit risk is one of the biggest challenges banks in Nigeria are faced with. By implication, it is also the one with dire consequences for their operation and survival, given the fact that a series of banks’ failures have significantly been brought into connection with nonperforming loans. Thus, this study examined the bank-specific and macroeconomic determinants of the nonperforming loans of the listed Deposit Money Banks (DMBs). Regression analysis involving fixed effect was adopted in order to analyze the panel data of the 10 selected deposit money banks in the period from 2008 to 2017. The findings show that the capital adequacy ratio, the size and the loans-to-total-assets ratio negatively and significantly affect nonperforming loans, whereas profitability and age were found to significantly but positively influence nonperforming loans of the Nigerian deposit money banks. More so, the liquidity ratio negatively, but insignificantly, affects nonperforming loans. However, not a single macroeconomic variable exerts a significant effect on nonperforming loans. The study recommends that banks should always deploy strategies for credit risk management by taking cognizance of the bank-specific and economic determinants of the nonperforming loans.